ANALISIS DIVERSIFIKASI VERTIKAL DAN NILAI TAMBAH PRODUK PRIORITAS PISANG PLANTAIN DI KABUPATEN BANYUWANGI (Analysis of Vertical Diversification and Value-Added of Priority Plantain Bananas Products in Banyuwangi Regency) - ENO, MOHAMMAD; NURHAYATI, NURHAYATI; KHOMSATIN, SITI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2026)
Bananas are a horticultural commodity that continues to grow in Banyuwangi. Bananas are categorized into two types: fruit/table bananas and processed/plantain bananas. This study aims to identify various vertical diversification potentials of plantain bananas, identify the most potential priority products of plantain bananas to be developed, and determine the added value of priority products from plantain bananas. This study utilizes two analytical methods: the Exponential Comparison Method (ECM) and Hayami's Value-Added Analysis. The results indicate that sale pisang (dried banana slices) is the most potential processed plantain product for further development and has a significant influence on market opportunity factors, capital, profit potential, and human resource capability. The results of the product value added analysis calculation are IDR 9,053.00/kg, with a relatively high value added ratio of 52%.